2020
DOI: 10.3390/ijerph17197205
|View full text |Cite
|
Sign up to set email alerts
|

What Is Rural Adversity, How Does It Affect Wellbeing and What Are the Implications for Action?

Abstract: A growing body of literature recognises the profound impact of adversity on mental health outcomes for people living in rural and remote areas. With the cumulative effects of persistent drought, record-breaking bushfires, limited access to quality health services, the COVID-19 pandemic and ongoing economic and social challenges, there is much to understand about the impact of adversity on mental health and wellbeing in rural populations. In this conceptual paper, we aim to review and adapt our existing underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
(70 reference statements)
0
31
0
Order By: Relevance
“…Indeed, it has been identified that rural paramedics require education and training specific to their needs, as rural practice has a focus on community rather than the types of cases [ 33 , 34 ]. This community focus is further explained in a recent Australian study that describes rural adversity as impacting mental health and wellbeing, requiring a collaborative and integrated approach with local leadership and community support [ 35 ]. Paramedics in rural areas have adopted a multidisciplinary approach to health care that has extended their role beyond specific skills, to include community engagement in primary health care, supporting various health disciplines and volunteers, and participating in education and training across health disciplines, also known as interprofessional learning [ 30 , 34 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been identified that rural paramedics require education and training specific to their needs, as rural practice has a focus on community rather than the types of cases [ 33 , 34 ]. This community focus is further explained in a recent Australian study that describes rural adversity as impacting mental health and wellbeing, requiring a collaborative and integrated approach with local leadership and community support [ 35 ]. Paramedics in rural areas have adopted a multidisciplinary approach to health care that has extended their role beyond specific skills, to include community engagement in primary health care, supporting various health disciplines and volunteers, and participating in education and training across health disciplines, also known as interprofessional learning [ 30 , 34 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of them studied the influence of isolation and rural adversity on mental health, describing a conceptual framework for this problem [ 9 ]. In the second one [ 10 ], the researchers analysed how the characteristics of the neighbourhood can influence poor mental health and how it is necessary to take them into account to develop national policies and programmes that influence and improve the health of residents.…”
Section: Resultsmentioning
confidence: 99%
“…and human resilience of communities and prevent the worst outcomes eventuating. 5 Mental ill health imposes a very high cost on individuals, communities and on Australia as a whole. This includes the enormous economic and emotional costs of providing mental health and support services.…”
Section: Social Determinantsmentioning
confidence: 99%
“…Human and physical losses are compounded by economic losses and the personal and business debts incurred might take many years to pay off. The emphasis on a range of interventions working together would increase the physical and human resilience of communities and prevent the worst outcomes eventuating 5 …”
Section: The Environmental and Social Determinantsmentioning
confidence: 99%